Clinical Efficacy of Qili Qiangxin Capsule Combined with Western Medicine in the Treatment of Chronic Heart Failure: A Systematic Review and Meta-Analysis. (9th August 2021) - Xu, Xiaoming; Yang, Yang; Zhou, Gendong; Du, Zhengxuan; Zhang, Xiaohong; Mao, Wei; Cai, Hongwen
Abstract : Qili Qiangxin capsule (QQC) is a formulation of traditional Chinese medicine commonly used for the treatment of heart failure in China. This meta-analysis aimed to assess the clinical efficacy of QQC combined with western medicine in the treatment of chronic heart failure (CHF). We conducted a systematic review and meta-analysis abided by the PRISMA guidelines. Literature search was conducted in the China National Knowledge Infrastructure, Wanfang Database, Chinese Scientific Journals Database, PubMed, and Web of Science from inception to August 2020. A total of 52 eligible studies were obtained, and 42 of these studies were included in the meta-analysis. The results showed that, compared with western medicine alone, the combination of Qili Qingxin capsule and Western medicine treatment has better efficacy (metoprolol: RR: 1.24, 95%CI 1.14–1.34; carvedilol: RR: 1.24, 95%CI 1.14–1.34; trimetazidine: RR: 1.20, 95%CI: 1.12–1.27; sacubitril valsartan sodium: RR: 1.23, 95%CI: 1.11–1.36; sodium nitroprusside: RR: 1.33, 95%CI: 1.23–1.45; and bisoprolol: RR: 1.31, 95%CI: 1.15–1.49) and increased the level of LVEF, LVEDD, and 6MWT of patients with CHF and reduced the adverse effects and the level of HR, LVESD, BNP, and Hs-cTnT as well. However, there is high heterogeneity in the meta-analysis of LVEDV, BNP, NT-proBNP, Hs-cTnT, 6MWT, and adverse effects, and the methodological quality of the included studies was poor. Therefore, further studies with good methodological quality and large sample size are required to validate our findings. In our study, evidence suggests that Qili Qiangxin capsule combined with Western medicine may improve therapeutic effect and the quality of life of patients with CHF.